2019
DOI: 10.1002/rrq.264
|View full text |Cite
|
Sign up to set email alerts
|

Using a Digital Spelling Game for Promoting Alphabetic Knowledge of Preschoolers: The Contribution of Auditory and Visual Supports

Abstract: The authors developed a digital spelling game to promote children's early literacy skills. Based on the dual‐coding theory, the authors studied the benefits of auditory support alone versus auditory+visual support. Children played the game in three conditions: no support, hearing the whole word; auditory‐only support, hearing a word segmented; and auditory+visual support, hearing the word segmented together with seeing the highlighted position of the letters. The participants were 129 Hebrew‐speaking children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…Self-efficacy was unrelated to in-game performance, and, therefore, mediation analysis was not performed. The effectiveness of GL Spelling could potentially be improved by improving children's response accuracy, for example, by provision of more explicit support for the phonological segmentation of the words, as was done in the study of Elimelech and Aram (2019), where the game spoke the word first normally, and then as segmented into different word parts, while highlighting the correct position of each letter on the screen. GL Spelling relied mostly on trial-and-error method (i.e., after incorrectly completed word, the learner was asked to try other letters until the word was correctly formed) instead of giving cues for the correct solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy was unrelated to in-game performance, and, therefore, mediation analysis was not performed. The effectiveness of GL Spelling could potentially be improved by improving children's response accuracy, for example, by provision of more explicit support for the phonological segmentation of the words, as was done in the study of Elimelech and Aram (2019), where the game spoke the word first normally, and then as segmented into different word parts, while highlighting the correct position of each letter on the screen. GL Spelling relied mostly on trial-and-error method (i.e., after incorrectly completed word, the learner was asked to try other letters until the word was correctly formed) instead of giving cues for the correct solution.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies conducted in non‐game‐based learning environments suggest that including PA and spelling training in early reading instruction is effective at improving children's reading and spelling skills (Ehri & Wilce, 1987; Santoro, Coyne, & Simmons, 2006; Uhry & Shepherd, 1993; Vandervelden & Siegel, 1997). Concerning game‐based studies, Elimelech and Aram (2019) found that a digital spelling game improved preschoolers early literacy skills, especially when the tasks included auditory and visual support, which helped children hear and see how words can be segmented into smaller phonological units. Also, Görgen, Huemer, Schulte‐Körne, and Moll (2020) evaluated the impact of a multicomponent digital game including training in PA, phoneme‐grapheme mapping, and word reading, on the reading skills of second and third graders with poor reading skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For studies that compared a technology intervention to a traditional intervention, seven reported improvements across both groups from pre-test to posttest with no significant difference between the group who had access to the technology-based intervention and the control group (Aunio & Mononen, 2018 ; Furman et al 2019 ; Oades-Sese et al, 2021 ; Outhwaite et al, 2020 ; Pan et al, 2021 ; Redondo et al, 2020 ; Simsek & Isikoglu Erdogan, 2021 ), while thirteen studies reported significant differences between technology and control groups with the group who had access to the technology-based intervention outperforming the control group on outcome measure (Amorim et al, 2020 ; Desoete & Praet, 2013 ; Hsiao & Chen, 2016 ; Korat et al, 2017 ; Martín et al, 2017 ; Maureen et al, 2018 ; Maureen et al, 2020 ; Muñoz-Repiso & Caballero-González, 2019 ; Papadakis et al, 2018 ; Schacter & Jo, 2017 ; Sullivan & Bers, 2018 ; Tang, 2020 ; Vatalaro et al, 2017 ; Wilkes et al, 2020 ). One study showed varying results across control and intervention groups, meaning that one group performed higher on certain skills than the other and vice-versa (Elimelech & Aram, 2020 ). For the included studies that employed a single-case research design, the results were mixed as well with most studies reporting an increase in target academic skills (Boyle et al, 2021 ; Chai, 2017 ; Musti-Rao et al, 2015 ), programming skills (Taylor, 2018 ), and engagement (McCoy et al, 2017 ) or social skills (Dueñas et al, 2021 ; Jung & Sainato, 2015 ; Pellegrino et al, 2020 ), while a few reported no clear, functional relation between the intervention and dependent variable (Cardon et al, 2019 ; Dennis et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Along with digitization, there is, as stressed by Hirsh-Pasek et al (2015), a need to exploit existing knowledge about learning processes in order to better support children's education (see also Brom, Sisler, & Slavik, 2010;Papadakis, Vaiopoulou, Kalogiannakis, & Stamovlasis, 2020) and, indeed, a number of studies have adopted this approach. For example, Elimelech and Aram (2020) developed a digital game aimed at promoting early literacy skills based on Paivio's dual-coding theory (see also Furio et al, 2012;Kyle, Kujala, Richardson, Lyytinen, & Goswami, 2013). The main aim of the present quasi-experiment, which compared the impact of digital games eliciting different learning processes, was to underpin the approach to game development with knowledge from the field of the learning sciences.…”
Section: Two Lines Of Inquirymentioning
confidence: 99%